Identification of Phytogenic Compounds with Antioxidant Action That Protect Porcine Intestinal Epithelial Cells from Hydrogen Peroxide Induced Oxidative Damage - Jing Wang; Meixia Chen; Sixin Wang; Xu Chu; Haifeng Ji (MDPI AG, 2022)
Oxidative stress contributes to intestinal dysfunction. Plant extracts can have antioxidant action; however, the specific phytogenic active ingredients and their potential mechanisms are not well known. We screened 845 phytogenic compounds using a porcine epithelial cell (IPEC-J2) oxidative stress model to identify oxidative-stress-alleviating compounds. Calycosin and deoxyshikonin were evaluated for their ability to alleviate H2O2-induced oxidative stress by measuring their effects on malondialdehyde (MDA) accumulation, reactive oxygen species (ROS) generation, apoptosis, mitochondrial membrane potential (MMP), and antioxidant defense. Nrf2 pathway activation and the effect of Nrf2 knockdown on the antioxidative effects of hit compounds were investigated. Calycosin protected IPEC-J2 cells against H2O2-induced oxidative damage, likely by improving the cellular redox state and upregulating antioxidant defense via the Nrf2-Keap1 pathway. Deoxyshikonin alleviated the H2O2-induced decrease in cell viability, ROS production, and MMP reduction, but had no significant effect on MDA accumulation and apoptosis. Nrf2 knockdown did not weaken the effect of deoxyshikonin in improving cell viability, but it weakened its effect in suppressing ROS production. These results indicate that the mechanisms of action of natural compounds differ. The newly identified phytogenic compounds can be developed as novel antioxidant agents to alleviate intestinal oxidative stress in animals.